Internet-Based Cognitive Behavioral Therapy for Depression and Anxiety Symptoms in Cancer: A Meta-Analysis - Cristina G., Domingo; Jessa Gilda P., Pandy; Marie Belle D., Francia (Asian Pacific Journal of Cancer Care, 2022)
Background: Depression and anxiety affect up to 20% of patients with cancer. Physical treatment and side effects are usually the only factors given attention to during treatment and recovery. Psychological distress can have deleterious effects in their quality of life, and may even affect healing. Treatment options for depression and anxiety are limited. One well-studied treatment is cognitive behavioral therapy (CBT). However, face-to-face treatment has been a challenge for the oncology team during this pandemic. Internet-based cognitive behavioral therapy (iCBT) can be a new means of dealing with cancer patients’ psychological health. Objective: To evaluate iCBT in alleviating depression and anxiety symptoms in patients with cancer. Methods: A systematic search of Pubmed, Embase, Cochrane, Clinical trials databases and hand search were utilized to identify randomized controlled trials (RCTs) investigating the role of iCBT in addressing psychological distress in cancer patients. Meta-analysis was conducted on 4 randomized controlled trials (N=548). All 4 studies were included for analysis. Psychological distress was measured as depression and anxiety based on the Hospital Anxiety and Depression Scale (HADS) total scores. Results: There was a trend in improvement of anxiety and depression in the iCBT treatment group, however, it was not significant (p = 0.06). Due to substantial heterogeneity, subgroup analyses was done and showed improvement of anxiety and depression in patients with different cancer types and baseline psychological distress (p < 0.00001). Conclusion: The results indicate that iCBT can be a potential treatment option in cancer patients who exhibit baseline depression and anxiety, especially during this pandemic. More studies are needed to determine the efficacy of iCBT in cancer patients who are not clinically diagnosed with psychological disorders.